1432 Tuberculosis and silicosis diagnostic crisis – a zimbabwe case series report - Moyo, D. (BMJ Publishing Group, 2022)
Introduction Zimbabwe has a long history of extensive hard rock mining and it is likely that the occupational lung disease (OLD) burden, for conditions such as silicosis and silico-tuberculosis, is huge. Poor access by miners to occupational health and safety services and lack of occupational health (OH) diagnostic skills against a background of a high tuberculosis burden in developing countries such as Zimbabwe presents a significant challenge in the diagnosis of pulmonary tuberculosis (PTB) and or silicosis amongst miners and ex miners.